Pengaruh Merokok Pasif Terhadap Insidensi Dismenore Primer - Amini, Raisa (Jurnal Kedokteran Indonesia, 2009)
Background: Primary dysmenorrhea is a common gynecologic disorder in women of reproductiveage. Primary dysmenorrhea can be defined as painful menstruation that occurs without pelvicabnormalities. Previous studies have found an association between current cigarette smoking andprevalence of primary dysmenorrhea. The purpose of this study was to examine the relationshipbetween the exposure to environmental tobacco smoke (ETS) and the occurrence of primarydysmenorrhea among women.Methods: This was a retrospective cohort study. The researchers conducted face-to-face interviewsusing a questionnaire to gather information. The study was held in 3 subdistricts in the city of Surakarta,including Jebres, Lawean and Pasar Kliwon. A total of 120 women sampled by fixed exposure samplingtechnique, participated in this study, consisting of 60 passive smoking women and 60 women who donot smoke. Data were analyzed by chi square and multiple logistic regression on SPSS 17.0.Results: The prevalence of primary dysmenorrhea was lower (p < 0.001) in unexposed women thanexposed women. Among women who were not exposed to smoke, 33.3% of them. Female passivesmokers were 23 times more likely than female non-smokers to suffer from primary dysmenorrhea(OR=23.0; 95% CI 7.8 to 67.2).Conclusion: Passive smoking is strongly associated with increased risk of primary dysmenorrhea amongwomen.Keywords : primary dismenorrhea, passive smokingï»¿